ANALISIS PRODUK KATERING SEHAT DI RUMAH SAKIT IZZA MENGGUNAKAN ST (SEGMENTING, TARGETING, POSITIONING) DAN 4P (PRODUCT, PRICE, PLACE, PROMOTION) - Agustian, Helmi (UI Scholars Hub, 2022)
The food industry (culinary business) is an industry that is always in demand by the public. During the current COVID-19 pandemic, public awareness of adopting a healthy lifestyle is increasing. Choosing a healthier diet is one way. Izza Hospital is one of the private hospitals in the Cikampek area, which has its Nutrition Installation Unit. As a hospital where most patients are BPJS, there has never been any development of new service products related to patient nutrition. The research conducted is descriptive. The primary data is collected by distributing questionnaires to 100 patients receiving treatment at outpatient care. The results of the customer segment analysis at Izza Hospital come from Karawang Regency (89%), travel time is less than <30 minutes (63%), and use private vehicles (89%). In terms of demographic factors, most of them are > 50 (39%), with female sex (64%), working as housewives (51%). Target customers are potential patients aged 20-39 years domiciled around hospitals with middle to lower economic class and female gender. The catering menu offered is balanced nutrition menu packages, healthy diet menu packages, and special diet menu packages.